Role of Medicinal Plants and Natural Products on Osteoporotic Fracture Healing. (2nd September 2012) - Abd Jalil, Mohd Azri; Shuid, Ahmad Nazrun; Muhammad, Norliza
Abstract : Popularly known as "the silent disease" since early symptoms are usually absent, osteoporosis causes progressive bone loss, which renders the bones susceptible to fractures. Bone fracture healing is a complex process consisting of four overlapping phases—hematoma formation, inflammation, repair, and remodeling. The traditional use of natural products in bone fractures means that phytochemicals can be developed as potential therapy for reducing fracture healing period. Located closely near the equator, Malaysia has one of the world's largest rainforests, which are homes to exotic herbs and medicinal plants. Eurycoma longifolia (Tongkat Ali), Labisia pumila (Kacip Fatimah), and Piper sarmentosum (Kaduk) are some examples of the popular ethnic herbs, which have been used in the Malay traditional medicine. This paper focuses on the use of natural products for treating fracture as a result of osteoporosis and expediting its healing.